Ir(III) Catalysis in N-Bromosuccinimide Oxidation of Lactic Acid in Perchloric Acid - Singh, B.N.; Prasad, Arjun; Singh, S.N. (Asian Journal of Chemistry, 2010)
Kinetic data on Ir(III) catalysed oxidation of lactic acid (LA) by N-bromosuccinimide (NBS) in perchloric acid in the presence of mercuric acetate as scavenger show first-order in each NBS, LA and Ir(III) and zero-order in [H+]. Negative effect of succinimide, positive effect of chloride ions and zero effect of ionic strength have been observed. Mechanistic steps are discussed.